Reducing damage extent of epoxy coating on magnesium substrate by Zr-enhanced PEO coating as an effective pretreatment - Z. Jamshidipour; M. Toorani; M. Aliofkhazraei; M. Mahdavian (Journal of Magnesium and Alloys, 2023)
This research was undertaken to study the effect of Zr-enhanced plasma electrolytic oxidation (PEO) as a pretreatment on the corrosion performance of epoxy coating applied on Magnesium in 3.5 wt.% NaCl solution. The parameters of delamination index along with coating damage index were extracted through electrochemical impedance spectroscopy (EIS) tests to determine how Zr may affect the corrosion protection of duplex PEO/epoxy coated samples. Pull-off adhesion tests were also accomplished to form a better understanding of Zr-enhanced PEO coating’ function. According to the obtained results, the presence of Zr can reduce the damage to the coating system by almost twice.